Hyperuricemia is Associated With 2- and 5-Year Adverse Outcomes in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention - Tang, Xiao-Fang; He, Chen; Zhu, Pei; Zhang, Che; Song, Ying; Xu, Jing-Jing; Yao, Yi; Xu, Na; Jiang, Ping; Jiang, Lin; Gao, Zhan; Zhao, Xue-yan; et al. (Frontiers in Endocrinology, 2022)
Background Despite hyperuricemia has been identified as independent risk factor for cardiovascular diseases, its prognostic value in the setting of ST-segment elevation myocardial infarction (STEMI) is still controversial. Although the mechanisms of this possible relationship are unsettled, it has been suggested that hyperuricemia could trigger the inflammatory response. This study sought to investigate the association between hyperuricemia with long-term mortality and with inflammatory response in patients with STEMI treated with percutaneous coronary intervention (PCI). Methods Blood samples were collected on admission of patients with STEMI: the inflammatory biomarkers high sensitive C-reactive protein (hs-CRP), erythrocyte sedimentation rate (ESR), and white blood cell (WBC) count were considered. Cumulative 2-years and 5-years mortalities were estimated using the Kaplan-Meier analysis. Multivariable analyses were performed by Cox proportional hazard models. Results In the 1448 patients with STEMI considered, 2-years mortality was 5.5% among patients with hyperuricemia and 1.4% among patient with normouricemia (P <0.001); 5-years mortality was 8.0% vs 3.9%, respectively (p =0.004). At multivariable analyses hyperuricemia was an independent predictor of 2-years mortality (hazard ratio (HR) =3.444, 95% confidence interval (CI): 1.621-7.319, P =0.001) and 5-years mortality (HR =1.896, 95% CI: 1.097-3.278, P =0.022). While, there were no difference of hs-CRP, ESR and WBC count on admission in patients with hyperuricemia compared to normouricemia (P >0.05). Conclusions Hyperuricemia was associated with higher 2-years and 5-years mortality in patients with STEMI undergoing PCI. While, our study was not found that hyperuricemia was associated with greater inflammatory response on admission in those patients.